Implementasi Penegakan Hukum Tindak Pidana Korupsi terhadap Lembaga Perkreditan Desa di Wilayah Hukum Resor Bangli - Arimastanaya, I Gede; Mahendrawati, Ni Luh Made; Sukandia, I Nyoman (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the procedures and implementation of law enforcement for corruption crimes against the misuse of Village Credit Institution (LPD) finances by the Indonesian National Police. This study uses an empirical legal research method with a sociological approach, which focuses on the study of the application of legal norms in law enforcement practices in society. The results of the study indicate that law enforcement against corruption crimes in LPDs is carried out through the stages of public complaints, investigations, inquiries, filing of Stage I and Stage II which in principle are in accordance with the provisions of laws and regulations, especially the Corruption Eradication Law, the Criminal Procedure Code, and the Law on the Indonesian National Police, and is guided by the internal Standard Operating Procedure (SOP) of the Indonesian National Police. However, the implementation of law enforcement has not been running optimally because it is faced with various obstacles, including differences in interpretation regarding the financial status of LPDs, limited resources of law enforcement officers, and the strong influence of social and cultural factors of indigenous village communities. Furthermore, the characteristics of LPD financial management, which is integrated with customary systems, create its own complexities in proving elements of state financial losses, thus requiring caution and professionalism from law enforcement officials and the support of authorized auditors. Therefore, law enforcement against corruption in LPDs should not only be oriented towards legal certainty and firm action, but must also consider the social context and local wisdom to achieve substantive justice, increase the deterrent effect, and encourage the realization of transparent, accountable, and equitable LPD governance for village communities.